Model Penduga Biomassa Hutan Mangrove Menggunakan Citra Satelit Sentinel -2A di Kabupaten Rembang Jawa Tengah - Ashari Ramadhan; Siman Suwadji (Jurnal Wana Tropika, 2023)
Mangrove forest is one of the forests that has the highest carbon storage in the tropics and is very high compared to the average carbon storage in various other forest types in the world, which contains around 1.023 Mg of carbon per hectare. This study aims to obtain a model for estimating the biomass potential of mangrove forests in Rembang Regency by utilizing Sentinel-2A Satellite imagery and making a map of the distribution of mangrove forest biomass potential through the best equation model. Sampling was done by purposive systematic sampling method. The correlation test results obtained a value of 0.640 which states that there is a strong relationship between biomass and NDVI. Biomass estimation modeling uses equation models namely Linear, Quadratic, Power, and Exponential. Model selection is done by considering several parameters such as R², RMSE, Bias, χ²-hit, SA, and SR. The selected model for estimating mangrove forest biomass potential is the quadratic model ???? = 17.4 -110.2 ???????????????? + 220 ????????????????² with an R² value of 0.474, RMSE value of 51.55, Chi-square test result of 3.46 and has the highest score value. The potential biomass distribution map generated from the selected model consists of 3 classes, namely classes < 3.7 (tons/ha), 3.7-10.5 (tons/ha), 10.5-35.7 (tons/ha). Mangrove forests in Rembang Regency have dominant biomass potential in the 10.5-35.7 (tons/ha) class.